Enhancing teacher education, development, and evaluation : lessons learned from educational reform - Lavigne, Alyson Leah; Good, Thomas L. (London: Routledge, 2019)
"Enhancing Teacher Education, Development, and Evaluation examines the complex role that recent educational reforms have played in the teaching profession. The failure of programs like Race to the Top to benefit teaching and learning outcomes has yielded many questions about what went wrong and how a research-based plan for true systemic progress could actually work. Covering inaccurate narratives about schools and student achievement, evidence for teacher effectiveness, and the history and repercussions of Race to the Top, this book culminates with a proposal for future research and policy initiatives that more accurately, equitably prioritize the measurement and improvement of teaching and learning. Five concise yet comprehensive chapters invite teacher and principal educators, teachers and school leaders in training, district administrators, policymakers, and other stakeholders to better understand the implications of and possible paths beyond misguided reform efforts. An overview of the recent past and an inspiration for the immediate future, this definitive analysis offers insights into how more reasonable, empirically derived strategies will ultimately foster more successful schools."--
Teaching in America: a paradox highly valued but lowly paid -- Teacher effects on student achievement: a review of the literature -- A brief history of education reform and race to the top -- Race to the top: its effects on principal practice, teaching, and learning -- Learning from failure.
Includes bibliographical references and index.
Keywords: Teachers -- United States; Teacher effectiveness -- United States; Educational change -- United States